(untitled) (Konferensiyalar | Conferences, 2024)
In the contemporary educational landscape, the integration of technology has revolutionized traditional pedagogical approaches, especially in general secondary education schools. This article explores the technological advancements that have facilitated the development of innovative methods to organize and deliver quality education in such institutions. From interactive learning platforms to data analytics for personalized learning, technology has catalyzed significant transformations in the educational sphere, ensuring enhanced engagement, accessibility, and effectiveness. This article underscores the pivotal role of technology in shaping the future of education and advocates for its strategic implementation to foster holistic student development and academic excellence